0
$\begingroup$

The scalar propagator for the Klein-Gordon Lagrangian is given by:

$$D(x-y)=\int \frac{d^{4} k}{(2 \pi)^{4}} \frac{e^{i k(x-y)}}{k^{2}-m^{2}+i \varepsilon}$$

I need to know if it is an even function, i.e.:

$$D(x-y) = D(-(x-y)) = \int \frac{d^{4} k}{(2 \pi)^{4}} \frac{e^{i k(x-y)}}{k^{2}-m^{2}+i \varepsilon}\tag{1}$$

Since $k^2=k_0^2-\vec{k}^2$ and $k_0^2$ and $\vec{k}^2$ are both positive.

Also

$$\int_{-\infty}^{\infty} d^4k e^{ik(x-y)}=\int_{-\infty}^{\infty} d^4k e^{-ik(x-y)}=\int_{-\infty}^{\infty} d^4k e^{ik(y-x)}$$

So can we conclude that equation 1 is indeed true?

edit: rephrased the question hope it makes sense now

$\endgroup$
  • 1
    $\begingroup$ Do you mean $D(x-y) = D(y-x)$ ? $\endgroup$ – Señor O Sep 29 at 17:50
  • 1
    $\begingroup$ I think you mean, when asking if it is even, if $D(x-y) = D(y-x)$ since what you've written cancels to $D(x-y)=D(x-y)$ which is obviously true. $\endgroup$ – JamalS Sep 29 at 17:52
  • $\begingroup$ Yes, it is true that $D(x-y) = D(-(y-x))$. $\endgroup$ – knzhou Sep 29 at 18:03
1
$\begingroup$

The fact that $D(x) = D(-x)$ follows immediately from the fact that the both the integrand and the integration measure are invariant under Lorentz transformations, and recalling that $x \to -x$ (parity transformation) is indeed a Lorentz transformation.

Alternatively, it's not difficult to prove it explicitly. \begin{align} D(-x) &= \int_{R^4}\frac{d^4k}{(2\pi)^4}\frac{e^{ik\cdot (-x)}}{k^2-m^2+i\varepsilon} \\ &= \int_{R^4}\frac{d^4k}{(2\pi)^4}\frac{e^{i(-k)\cdot x}}{k^2-m^2+i\varepsilon}. \end{align} Now make the substitution $k' = -k$. Since $|\det(\partial k'/\partial k)|=|-1|=1$ and under this substitution $R^4$ gets mapped into itself, we have, by substitution for multiple variables, \begin{align} \phantom{D(-x)} &= \int_{R^4}\frac{d^4k'}{(2\pi)^4}\frac{e^{ik'\cdot x}}{(-k')^2-m^2+i\varepsilon} \\ &= \int_{R^4}\frac{d^4k'}{(2\pi)^4}\frac{e^{ik'\cdot x}}{k'^2-m^2+i\varepsilon} \\ &= D(x) \end{align} (since $k'$ is just a dummy variable; we also used the fact that $(-k)^2 = k^2$).

Hope that this doesn't get through as too pedantic, and possibly clarifies! Cheers

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.